Association of HLA class I markers with multiple sclerosis in the Italian and UK population: evidence of two independent protective effects. Issue 7 (25th March 2011) - Bergamaschi, Laura; Ban, Maria; Barizzone, Nadia; Leone, Maurizio; Ferrante, Daniela; Fasano, Maria Edvige; Guerini, Franca R; Corrado, Lucia; Naldi, Paola; Dametto, Ennia; Agliardi, Cristina; Salvetti, Marco; et al.
Abstract : Background: The association of HLA A*02 with multiple sclerosis (MS) was recently confirmed by the authors, and it was observed that the combined presence of HLA Cw*05 significantly enhanced (threefold) the protective effect of HLA A*02 . Objectives and methods: Since A*02 - Cw*05 is carried by two HLA extended haplotypes characterised by the B*4402 and B*1801 alleles, respectively, the association analysis was extended to HLA B*44 and B*18 in an Italian sample (1445 MS cases and 973 controls) and these associations were verified in a UK cohort (721 MS cases, 408 controls and 480 family trios). Results: A strong protective effect, independent of DR15, of the A*02 - Cw*05 combination carrying B*44 (OR 0.27, p=3.3×10 -5 ) was seen in the Italian samples and confirmed in UK family trios (OR 0.33, p=5.5×10 -4 ) and in a combined cohort of UK families and case–controls (OR 0.53, p=0.044). This protective effect was significantly stronger than that mediated by A*02 alone. Logistic regression showed that A*02 - Cw*05 maintained a significant protection when adjusted for B alleles (Italy: OR 0.38, p=6.5×10 -7 ; UK: OR 0.60, p=0.0029), indicating that it was not secondary to linkage disequilibrium with B*44 . Different from A*02, the other HLA class I tested markers individually showed no significant ( Cw*05, B*18) or a modest (B*44) protection when adjusted for the remaining markers. Conclusions: This study identified at least two independent protective effects which are tagged by A*02–Cw*05 and A*02, respectively. Further studies are needed to elucidate whether this protective effect is due to the presence of an unanalysed factor characterising the HLA extended haplotype(s) carrying A*02 and Cw*05 or to a direct interaction between these alleles.